2022
DOI: 10.3390/cells11091538
|View full text |Cite
|
Sign up to set email alerts
|

To Detach, Migrate, Adhere, and Metastasize: CD97/ADGRE5 in Cancer

Abstract: Tumorigenesis is a multistep process, during which cells acquire a series of mutations that lead to unrestrained cell growth and proliferation, inhibition of cell differentiation, and evasion of cell death. Growing tumors stimulate angiogenesis, providing them with nutrients and oxygen. Ultimately, tumor cells invade the surrounding tissue and metastasize; a process responsible for about 90% of cancer-related deaths. Adhesion G protein-coupled receptors (aGPCRs) modulate the cellular processes closely related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…ALCAM is involved in the adhesion and migration of cancer cells and the interaction between cancer cells and immune cells [47,48]. In contrast, Adgre5 modulates the interaction between cancer cells and immune cells by suppressing the immune response [49]. Therefore, targeting these proteins could disrupt the interaction between cancer cells and the microenvironment, leading to decreased tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…ALCAM is involved in the adhesion and migration of cancer cells and the interaction between cancer cells and immune cells [47,48]. In contrast, Adgre5 modulates the interaction between cancer cells and immune cells by suppressing the immune response [49]. Therefore, targeting these proteins could disrupt the interaction between cancer cells and the microenvironment, leading to decreased tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing of ADGRE5 mRNA generates three distinct isoforms that differ in the number of epidermal growth factor (EGF)-like repeats in the N-terminal extracellular domain (ECD) of the receptor ( Figure 1M ). 25 Analysis of TCGA RNA-seq data indicated that isoform 3, with four EGF repeats in the N-terminus, is the predominant variant in GBM ( Figure 1N ). CD97 transcript was found in all transcriptional subtypes of GBM in TCGA ( Supp.…”
Section: Resultsmentioning
confidence: 98%
“…CD97 is expressed in several lineages of the immune system, where it is critical for the inflammatory response, [20][21][22][23][24] as well as in multiple liquid and solid malignancies. 13,[25][26][27][28] Among these malignancies is GBM, in which CD97 was previously implicated in cellular proliferation, brain invasion, and tumor metabolism. [29][30][31][32][33] However, its mechanism of action in GBM remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…One of the key issues in treating cancer is to prevent tumor cells from invading and metastasizing ( 38 ). The scratch assay and Transwell assay were applied to detect the effect of BJP-2 on the migration of HepG-2 cells.…”
Section: Resultsmentioning
confidence: 99%